Study of bacterial interactions in reconstituted hydrocarbon-degrading bacterial consortia from a local collection, for the bioremediation of weathered oily-soils - Shaikha Y. Alsayegh (16931769) (2021)
To enhance the process of bacterial remediation of weathered hydrocarbons, the area of Dukhan, Qatar, was considered as a model for weathering processes. Self-purification by indigenous hydrocarbondegrading bacteria showed low performance. Biostimulation/seeding using one or another of the indigenous bacteria improved the performance. Symbiosis between three strains dominating the soil; Bacillus sorensis D11, Bacillus cereus D12, and Pseudomonas stutzeri D13, was highly performant for removal of total petroleum hydrocarbons in the weathered soil. D11, the most sensitive, showed the highest performance when mixed with D12 or D13. D12, less performant than D11, was more active on diesel range organics (DRO: C10-C28), similar to D11. D13 showed a metabolic behavior close to commensal and co-metabolic ones. It was more active on hydrocarbons above C29. Combination of the three strains conducted to the removal of at least 80% of C10-C35 organics in the extract at concentrations of 31.1 mg/g TPH-DRO. Other Information Published in: Biotechnology Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.btre.2021.e00598